2016
DOI: 10.1097/scs.0000000000002206
|View full text |Cite
|
Sign up to set email alerts
|

Treatment for Infantile Hemangiomas

Abstract: The authors present a series of patients with IH safely treated with 2 mg/kg/d of propranolol. Using a strict protocol, few complications were observed. Patients achieved significant reduction in size and improvement of the overall appearance of IH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 18 publications
0
8
0
Order By: Relevance
“…The majority of growth occurs before 12 weeks, after which growth velocity decreases and usually ceases between 4 and 6 months. Deep IHs appear somewhat later and grow somewhat longer than their superficial counterparts (on average, approximately 1 month more) 3 4 5 . Large, deeply penetrating lesions (particularly in the parotid area) can grow until the patient is 2 years of age 6 but subsequently partially or completely disappear in 30% of patients by 3 years of age, 20% of patients by 5 years, and 30–40% of patients by 9 years; however, these lesions remain unchanged in 10–20% of patients 7 .…”
Section: Discussionmentioning
confidence: 95%
“…The majority of growth occurs before 12 weeks, after which growth velocity decreases and usually ceases between 4 and 6 months. Deep IHs appear somewhat later and grow somewhat longer than their superficial counterparts (on average, approximately 1 month more) 3 4 5 . Large, deeply penetrating lesions (particularly in the parotid area) can grow until the patient is 2 years of age 6 but subsequently partially or completely disappear in 30% of patients by 3 years of age, 20% of patients by 5 years, and 30–40% of patients by 9 years; however, these lesions remain unchanged in 10–20% of patients 7 .…”
Section: Discussionmentioning
confidence: 95%
“…[1] IHs usually manifest during the 1 st month of life and the proliferative phase extends for the first 2 years of age. [2] These hemangiomas may be disfiguring but are not usually life-threatening or function impairing, and most clinicians emphasize an approach of observation before any intervention. Most IHs involute spontaneously in the first decade of life after the 2 nd year.…”
Section: Introductionmentioning
confidence: 99%
“…Although propranolol treatment can be efficacious beyond the proliferative phase, irreversible skin changes may have already occurred. In addition, recent studies have demonstrated that early treatment, especially when started during the proliferating phase, has been shown to be associated with better long-term outcomes 12, 13 . Therefore, for the IHs needing treatment, the ideal time to initiate therapy is either before or as soon as the evidence of permanent anatomic distortion or medical sequelae develop.…”
Section: Introductionmentioning
confidence: 99%